2022
DOI: 10.1002/jbm.a.37378
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated insulin‐like growth factor‐1 biotherapeutic delivery promotes rotator cuff regeneration in a rat model

Abstract: Tears in the rotator cuff are challenging to repair because of the complex, hypocellular, hypovascular, and movement‐active nature of the tendon and its enthesis. Insulin‐like Growth Factor‐1 (IGF‐1) is a promising therapeutic for this repair. However, its unstable nature, short half‐life, and ability to disrupt homeostasis has limited its clinical translation. Pegylation has been shown to improve the stability and sustain IGF‐1 levels in the systemic circulation without disrupting homeostasis. To provide loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…8e). The recent study reported IGF1 from macrophages could promote muscle regeneration and IGF1 could heal tendon lesion [53][54][55] . MP3 may inhibit fibrosis by IGF1 through MAPK signaling pathway to promote tendon healing.…”
Section: Deciphering the Intricate Interplay Among Multiple Cell Line...mentioning
confidence: 99%
“…8e). The recent study reported IGF1 from macrophages could promote muscle regeneration and IGF1 could heal tendon lesion [53][54][55] . MP3 may inhibit fibrosis by IGF1 through MAPK signaling pathway to promote tendon healing.…”
Section: Deciphering the Intricate Interplay Among Multiple Cell Line...mentioning
confidence: 99%
“…Insulin-like growth factor 1 (IGF-1) facilitates the production of aggregation proteins and reduces their catabolism, but unmodified IGF-1 has a short half-life and can easily diffuse outside of the joint, leading to unfavorable side effects (Tyler, 1989;Shi et al, 2020;Prabhath et al, 2022). Sustained and local delivery of IGF-1 to cartilage can come true by combining the heparin-binding epidermal growth factorlike growth factor (HB-EGF) with IGF-1 to generate heparinbinding insulin-like growth factor 1 (HB-IGF-1) (Mujeeb et al, 2013;Sarkar et al, 2019;Zhang X. et al, 2021).…”
Section: Growth Factorsmentioning
confidence: 99%
“…It is known to regulate both anabolic and catabolic pathways in skeletal muscle [ 15 ], aid ageing processes (together with GH), and act synergistically with PDGF-BB in cell cultures aimed at tendon tissue engineering [ 16 ]. Moreover, several approaches including IGF-1 in tendon healing have been successful [ 17 ], i.e., reaching earlier functional recovery of a rat’s Achilles tendon [ 18 ] or a rat’s rotator cuff tendon [ 19 ], resulting in higher cell proliferation and collagen content in IGF-1-treated equine flexor tendinitis [ 20 ] or increased tendon biomechanics in rabbit patellar tendons in combination with TGF-β [ 21 ]. In addition, activation of the IGF1R (receptor for IGF-1) and MAPK signaling by a phytoestrogen has recently been reported to support tendon healing in a rat Achilles tendon model [ 22 ], demonstrating the positive effect of these signaling cascades that are also activated through IGF-1 binding to IGF1R.…”
Section: Introductionmentioning
confidence: 99%